2004
DOI: 10.1007/s00192-004-1209-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of outcomes of transurethral versus suprapubic catheterization after Burch cystourethropexy

Abstract: The objective of this study was to evaluate the outcomes of patients with transurethral vs suprapubic catheterization after Burch cystourethropexy. This is a retrospective cohort study of patients who had an anti-incontinence procedure primarily including Burch cystourethropexy with hysterectomy or Burch alone between July 1997 and June 2002 and comparing the outcomes of transurethral vs suprapubic catheters. The suprapubic and transurethral catheter placed were both 16-Fr Foley catheters. The variables analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…This difference remained after adjusting for possible confounders such as preoperative PVR, concomitant hysterectomy, and concomitant anti-incontinence surgery. This finding is consistent with a longer length of catheterization found in other studies when comparing SPC with TUC after pelvic reconstructive surgery 10 . The baseline difference in concomitant anti-incontinence procedures and concomitant hysterectomies reflected surgeon preference and was not due to preoperative concerns for voiding function postoperatively.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This difference remained after adjusting for possible confounders such as preoperative PVR, concomitant hysterectomy, and concomitant anti-incontinence surgery. This finding is consistent with a longer length of catheterization found in other studies when comparing SPC with TUC after pelvic reconstructive surgery 10 . The baseline difference in concomitant anti-incontinence procedures and concomitant hysterectomies reflected surgeon preference and was not due to preoperative concerns for voiding function postoperatively.…”
Section: Discussionsupporting
confidence: 89%
“…Options for managing postoperative transient urinary retention include indwelling transurethral catheter (TUC), clean intermittent catheterization (CIC), and planned suprapubic catheter (SPC) placement at the time of prolapse repair. Each option has unique advantages and disadvantages to include urinary tract infection (UTI) risk, ease of patient use, and patient comfort 7–11 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their opinion was that shorter catheterization was equivalent if not better. Dunn et al [12] retrospectively reviewed 217 patients who were managed postoperatively with either a suprapubic (106) or a urethral (111) catheter to see if this affected the outcome of the procedure. There were no differences in cure rates and the only statistical differences were with greater pain and shorter length of catheterization in the urethral group.…”
Section: Postoperative Catheterizationmentioning
confidence: 99%
“…Evidence has illustrated that suprapubic catheter may bring more benefits for patients compared to transurethral catheter. A retrospective cohort study showed that patients with suprapubic catheter had less clinical visits due to pain than ones with indwelling urethral catheter [17]. The result from a metaanalysis revealed that suprapubic catheterization was associated with a significant lower risk of bacteriuria and less discomfort compared with transurethral catheter [18].…”
Section: Renal Failurementioning
confidence: 99%